Treatment Courses of Patients Newly Diagnosed with Multiple Sclerosis in 2012-2018 - Sipilä Jussi OT (MDPI, 2025)
Treatment options for multiple sclerosis (MS) are now numerous, but it is unclear which Disease-Modifying Treatment (DMT) is the optimal choice for a given patient. Treatment switches are common, both because of side effects and because of lack of efficacy. There are few data available on the treatment courses of patients newly diagnosed with MS in the current DMT era. All patients newly diagnosed with MS in 2012-2018 at North Karelia Central Hospital were identified (N = 55), and those with complete follow-up data available (N = 43) were included. The minimum follow-up from diagnosis was 44 months with a maximum of 9 years. Seven patients (16%) had no DMT at any time during the follow-up. Treatment was most often initiated with interferon or glatiramer acetate (69%), but 72% of these treatments were discontinued. After cladribine, teriflunomide and fingolimod showed the best treatment persistence. Patients who experienced their first MS symptoms at >= 40 years of age all continued with their initial treatment category until the end of the follow-up. In a third of the patients who had received a DMT, at the end of the follow-up, the treatment had been escalated to fingolimod, cladribine or natalizumab. Only 13 patients (28%) continued with their initial DMT until the end of the follow-up.